Capabilities of delayed microsurgical reconstruction in patients with squamous cell carcinoma of the buccal mucosa: clinical case - A. O. Guz; A. V. Garev; D. M. Fatkullin; A. S. Zaharov; M. I. Sokolova (Опухоли головы и шеи)
Surgical treatment of patients with locally advanced squamous cell carcinoma of the oral mucosa is a complicated problem requiring maximal surgical radicality and, at the same time, single-stage reconstruction to preserve organ function and achieve acceptable esthetic results. One of modern reconstruction techniques is the use of free flaps. Application  of  this  technique  requires  microsurgical  skills  from  the  surgeon.  unfortunately,  it  is  not  always  possible to achieve the result after single-stage postoperative defect closure. Sometimes unforeseen complications are observed: necrosis of the moved flaps, formation of large postoperative defects, orostomas, pharyngostomas. In such cases, oncologists  face  a  more  complicated  problem:  defect  reconstruction  in  the  conditions  of  pronounced  scarring  process in the intervention area, development of post-radiation fibrosis and soft tissue edema.The presented clinical case demonstrates the capabilities of repeat microsurgical reconstruction in patients with orostoma developed after unsuccessful primary reconstruction.